2011
DOI: 10.1007/s10661-011-2129-0
|View full text |Cite
|
Sign up to set email alerts
|

Determination of noise induced hearing loss in mining: an application of hierarchical loglinear modelling

Abstract: The levels of noise arise from mining industry seem to be higher when compared to other industries. For this reason, noise exposure and noise-induced hearing loss (NIHL) are prevalent in mining. Assessment of noise emission levels that arise from various mining operations is required to prevent and minimize the NIHL. Because the studies for preventing occupational hearing loss among miners are inadequate, a quarry and stone crushing-screening plant was selected to generate site-specific data. The noise levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 8 publications
0
7
0
14
Order By: Relevance
“…Except for one study that takes place in the construction field (Lee, Kim, & Hong, 2019), every other paper set is related to the mining industry, where the exploited commodities varied between marble (Melo Neto, Kohlman Rabbani, Barkokébas Junior, Lago, & Jonathas, 2012) to aggregates (Onder, Onder, & Mutlu, 2012) and andesite (Kosała & Stępień, 2016), limestone (Çınar & Şensöğüt, 2019), coal (Simion, Kovacs, Toth, Ilie, & Gireadă, 2017) and lignite (Srivastava, Gupta, Srivastava, & Kaur, 2010), chromite (Kerketta, Gartia, & Bagh, 2012), copper (Lilic et al, 2018) and iron (Lokhande et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Except for one study that takes place in the construction field (Lee, Kim, & Hong, 2019), every other paper set is related to the mining industry, where the exploited commodities varied between marble (Melo Neto, Kohlman Rabbani, Barkokébas Junior, Lago, & Jonathas, 2012) to aggregates (Onder, Onder, & Mutlu, 2012) and andesite (Kosała & Stępień, 2016), limestone (Çınar & Şensöğüt, 2019), coal (Simion, Kovacs, Toth, Ilie, & Gireadă, 2017) and lignite (Srivastava, Gupta, Srivastava, & Kaur, 2010), chromite (Kerketta, Gartia, & Bagh, 2012), copper (Lilic et al, 2018) and iron (Lokhande et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Given that this study's aim is related to occupational exposure to noise, the experimental data was classified according to the measurement setting, which is provided in Table 1, divided into activity, equipment, job category, and working area. (Srivastava et al, 2010) x (Gupta, Roy, & A. Rajan B, 2012) x (Kerketta et al, 2012) x (Melo Neto et al, 2012) x (Onder et al, 2012) x (Cinar & Sensogut, 2013) x (Gyamfi, Amankwaa, Owusu Sekyere, & Boateng, 2016) x (Kosała & Stępień, 2016) x x (Lokhande et al, 2017) x (Simion et al, 2017) x (Lilic et al, 2018) x (Wichers et al, 2018) x (Çınar & Şensöğüt, 2019) (Lee et al, 2019) x (Mihut, 2019) x…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown age decrements in performance of sustained attention tasks. Onder et al, (2012) studied NIHL in mines at Turkey. They had applied statistical analysis (hierarchical log-linear) of the data.…”
Section: Introductionmentioning
confidence: 99%